(untitled) (International Journal of Pharmaceutical and Life Sciences, 2014)
The galacotsylated albumin nanoparticles were prepared for the selective delivery of Cimetidine to the asialoglycoprotein receptor (ASGP-R) which is particularly presents on mammalian hepatocytes. The albumin nanoparticles (NPs) were prepared by using desolvation method and efficiently conjugated with galactose. Various parameters such as particle size, % entrapment efficiency and drug loading efficiency, percentage yield, in vitro drug release, were determined. The size of nanoparticles (both plain and galactose coated) was found to be in range of 200-250 nm, and maximum drug payload was found to be 19.08% ± 1.10 .The maximum drug content was found to be 30.80% ± 0.3 and 27.09% ± 0.5 respectively in plain and galactose coated nanoparticles while the maximum entrapment efficiency was found to be 90.68% ± 0.5 and 91.75% ± 0.59 in plain and coated nanoparticles. It was also found that coating of nanoparticles increases the size of nanoparticles. From the in-vitro studies, it was concluded that increase in polymer concentration, decreases the drug releases from the nanoparticles. DOI: http://dx.doi.org/10.3329/ijpls.v2i5.17628 International Journal of Pharmaceutical and Life Sciences, Volume 2(5) Dec 2013: 202-229